PENGARUH HARGA DAN PELAYANAN KONSUMEN TERHADAP KEPUTUSAN PENGGUNAAN JASA APLIKASI GRAB (STUDI PADA KONSUMEN GRAB KOTA BIMA) - Apriansyah; Ernawati, Sri (Lembaga Pengembangan Kinerja Dosen, 2022)
Grab, which is also known as MyTeksi abroad, is one of the online transportation applications in Indonesia. He is present as one of the successful startups in reaching consumers in Indonesia. The convenience provided by this one application is quite real. To analyze that price, consumer service has a significant influence on the decision of users of the Grab Application Service (Study on Grab Consumers in Bima City). This type of research includes associative research. The population used is all consumers who have used Grab services in the city of Bima, the number of which is not known for certain (Unknown population). The number of samples is 50 people. The sampling technique in this research is purposive sampling. Analysis of research data using SPSS version 26. The data analysis techniques used to answer the hypothesis are Validity and Reliability Test, Classical Assumption Test, Multiple Linear Regression, Multiple Correlation Coefficient Analysis, Coefficient of Determination, T Test (Partial), F Test (Simultaneous). ). The results of the study state that price, consumer services have a significant influence on the decision of users of the Grab Application Service (Study on the Bima City Grab Consumer) both partially and simultaneously.